Specifying the procedure for designing the elements of the crankshaft system for a small high-speed diesel engine - Abramchuk, Fedor; Grytsyuk, Oleksandr; Prokhorenko, Andrei; Reveliuk, Ivan (Eastern-European Journal of Enterprise Technologies, 2018)
Development of the model range of high-speed inline small diesels by designing a six-cylinder version based on the already adjusted four-cylinder one, entails a decrease in the rigidity of the crankshaft. This in turn reduces its reliability due to the enhanced impact of torsional vibrations. To assess this impact, we performed a series of calculations for determining the amplitudes and tangential stresses in the crankshaft system. In order to reduce maximum values of angular amplitudes and tangential stresses, the most expedient is to use a silicone damper for absorbing the torsional vibrations. When designing it, one must take into consideration such structural parameters as the efficiency of damping and overall dimensions. In the course of this study, we performed the estimation of torsional vibrations using the new simple method for calculating the real amplitudes and mechanical stresses of torsional vibrations in the crankshaft of the internal combustion engine. A given method is based on the numerical solution to the high-level system of nonlinear differential equations in the form of a model in the state space. In addition, in the process of determining the initial data, we proposed a formula for determining the rigidity of the crank shaft. The improvement implied the introduction of a coefficient that approximates values obtained by calculation to those derived experimentally. This adjustment applies only for the crankshafts with similar parameters of cranks. During our study, we selected criteria that are used when designing the elements of the crankshaft system. That made it possible to determine, based on these criteria, the following structural characteristics for the designed diesel engine: the mass moment of inertia of the damper flywheel, the mass moment of inertia of the damper casing, as well as the diameter and rigidity of the crankshaft front end. Our research helps create an algorithmic support that can be employed when designing diesel engines with similar geometrical dimensions and forcing in the future.